-(v-3)=-5

Simple and best practice solution for -(v-3)=-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(v-3)=-5 equation:



-(v-3)=-5
We move all terms to the left:
-(v-3)-(-5)=0
We add all the numbers together, and all the variables
-(v-3)+5=0
We get rid of parentheses
-v+3+5=0
We add all the numbers together, and all the variables
-1v+8=0
We move all terms containing v to the left, all other terms to the right
-v=-8
v=-8/-1
v=+8

See similar equations:

| -12x^2-108x=0 | | 112=3y | | 10a+5=25 | | -16=2(x+6) | | 3/4=3-5+4b/12 | | 2t=(6t-3) | | 4(y-2)=7y+2-2(-6y-1) | | -3/5x+1=-7 | | -3(x+7)+4x=-15 | | 30X8.75+11p=400 | | (8/15)*(2/13)=x | | 4y-8=19y+4 | | 7x+42=11(3x+8)-2(13x-1) | | (-4x+5)-(6x-7)=0 | | w+18w=-17 | | 2r+-6=0 | | -2/x-8=3 | | 3.8+10m=8.39 | | x(-21)=-3 | | 21y-72=8y-8 | | 7(x-4)+3(x+5)=2x-2 | | 22-4m=18 | | 42x^2+68x=-18 | | 100=5-1x | | -3=7/w+6 | | 12=4(k-15) | | 1=n-18/2 | | 3-s=-14 | | -12d/d=3 | | 11y-8=3y-22 | | Z(r-3)/4-8=50 | | j+3/3=4 |

Equations solver categories